Chapter 7. Hybrid green aerogels: processing and morphology - Kien-Woh, Kow; Yusoff, Rozita (Royal Society of Chemistry, 2018)
Hybrid bio-based aerogels exhibit enhanced synergistic properties as compared to their corresponding constituents. The technology has attracted increasing research interests, particularly as these syntheses lead to formation of various microstructures with different properties of the composite. In this chapter, the recent developments in hybrid bio-based aerogels are introduced, including the use of new precursors, doping techniques, and microstructure, as well as morphology of composites. Applications of the new precursors such as collagen, xyloglucan, pectin, lignin, aniline, polypyrrole, graphene oxide and halloysite nanotubes are discussed separately. Detailed syntheses of hybrid bio-based aerogels are elaborated in the stages of sol formation, gelation, doping and drying. Micrographic images are categorized based on the microstructures of the hybrid aerogels, where the formation of each type of microstructure is illustrated and discussed. At the end of the chapter, a new technique, called synchrotron X-ray tomography is introduced, which is able to probe the degree of anisotropy of the hybrid aerogels. © The Royal Society of Chemistry 2018.